Using Population-Size Estimation and Cross-sectional Survey Methods to Evaluate HIV Service Coverage Among Key Populations in Burkina Faso and Togo. (November 2016) - Holland, Claire E.; Kouanda, Seni; Lougué, Marcel; Pitche, Vincent Palokinam; Schwartz, Sheree; Anato, Simplice; Ouedraogo, Henri Gautier; Tchalla, Jules; Yah, Clarence S.; Kapesa, Laurent; Ketende, Sosthenes; Beyrer, Chris; et al.
Objectives: The objective of our study was to measure progress toward the UNAIDS 90-90-90 HIV care targets among key populations in urban areas of 2 countries in West Africa: Burkina Faso and Togo. Methods: We recruited female sex workers (FSWs) and men who have sex with men (MSM) through respondent-driven sampling. From January to July 2013, 2738 participants were enrolled, tested for HIV, and completed interviewer-administered surveys. We used population-size estimation methods to calculate the number of people who were engaged in the HIV continuum of care. Results: HIV prevalence ranged from 0.6% (2 of 329) of MSM in Kara, Togo, to 32.9% (115 of 350) of FSWs in Bobo Dioulasso, Burkina Faso. Of those confirmed to be HIV infected, a range of 0.0% (0 of 2) of MSM in Kara to 55.7% (64 of 115) of FSWs in Bobo Dioulasso were using ART. Based on population estimates, the percentage gap between HIV-infected people who should be using ART (per the 90-90-90 targets) and those who reported using ART ranged from 31.5% among FSWs in Bobo Dioulasso to 100.0% among MSM in Kara. Conclusions: HIV service coverage among MSM and FSWs in Burkina Faso and Togo was low in 2013. Interventions for improving engagement of these at-risk populations in the HIV continuum of care should include frequent, routine HIV testing and linkage to evidence-based HIV treatment services. Population-size estimates can be used to inform governments, policy makers, and funding agencies about where elements of HIV service coverage are most needed.